Museu Amazônico: guia para a exposição de longa duração - Siqueira, Thiago Giordano de Souza (Brasil, 2025)
This material was produced with the aim of supporting educational actions and information from the Museum's long-term exhibition Amazonian titled “Amazonian Museum: memory and identity”. It is hoped that the texts presented can help to understand the exposure and, if you are a teacher, you can propose ways to bring people together themes covered in the classroom with students. It is a product inspired and processed during doctoral research in Information Science, entitled “Information Mediation in museums: conceptions based on texts from the exhibition long-term exhibition at the Amazon Museum of the Federal University of Amazonas” developed within the scope of the Postgraduate Program in Information Science at the São Paulo State University (PPGCI/UNESP).